Crystal Structures of Metal Complexes - Sakiyama, Hiroshi (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint contains 11 papers published in a Special Issue of Molecules entitled "Crystal Structures of Metal Complexes". I will be very happy if readers will be interested in the crystal structures of metal complexes.